The 2016 Tips From Former Smokers® Campaign: Associations With Quit Intentions and Quit Attempts Among Smokers With and Without Mental Health Conditions. Issue 5 (28th November 2018) - Prochaska, Judith J; Gates, Emily F; Davis, Kevin C; Gutierrez, Karen; Prutzman, Yvonne; Rodes, Robert
Abstract: Introduction: People living with mental health conditions (MH+) are more likely to smoke cigarettes than people without mental health conditions (MH−) and to experience tobacco-related disparities. The Tips From Former Smokers ® ( Tips ®) campaign is a proven population-level strategy for motivating smokers to quit. In 2016, Tips included ads featuring Rebecca, a former smoker with depression. We evaluated self-reported frequency of exposure to the Rebecca and other Tips ads in association with quit intentions and quit attempts among MH+ and MH− smokers. Methods: Intentions to quit and past 6-month quit attempts lasting at least 24 hours were reported from a two-wave longitudinal online survey conducted before and after the 2016 Tips campaign with a nationally representative sample of US adult cigarette smokers with (MH+, N = 777) and without (MH−, N = 1806) lifetime mental health conditions. Results: In 2016, among MH+ respondents, greater exposure to the Rebecca ads was significantly associated with increased odds of intending to quit in the next 30 days (adjusted odds ratio [AOR] = 1.40, p < .05) and with reporting a quit attempt in the past 6 months (AOR = 1.25, p < .05). Among MH− respondents, greater exposure to the other Tips ads was associated with increased odds of making a quit attempt (AOR = 1.19, p < .05). Conclusions: Exposure to the Rebecca ads was associated with a greater likelihood of intentions to quit and quit attempts among MH+ smokers; whereas, exposure to the other (non-mental-health-related) Tips ads was associated with a greater likelihood of quit attempts among MH− smokers. Implications: National media campaigns are an important population-level strategy for reaching specific population groups who are experiencing tobacco-related disparities. The findings support the inclusion of ads featuring people living with mental health conditions in national tobacco education media campaigns, such as Tips .